THE EUROPEAN AVIATION POST-COVID-19 SCENARIO: OBSERVATIONS AND PERSPECTIVES - Hobe, Stephan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The goal of this article is to present the observations of the main impacts of the COVID-19 pandemic on European air transport, as well as to highlight possible scenarios and perspectives for aviation industry restoring. The article focuses on the European Union Reaction on such impacts. Besides, the article highlights outlines measures and packages to mitigate COVID-19’s effects on air services. Research methods: the research was carried out using generally accepted methods of scientific knowledge, such as: analytical, comparative-legal, systemic-structural, statistics and others. Results: as a result of academic research, the main impacts of the COVID-19 on European aviation were revealed, current measures of the European Union and International organizations were outlined and post-Covid-19 scenario and perspectives in the European aviation industry were presented. Discussion: the COVID-19 pandemic impacted on European air transport and caused an unprecedented and unparalleled stall in air traffic, with an overall reduction of international passengers estimated between 50 and 80% in the first months of 2020 as compared to 2019. Besides forecasts do not predict a fast recovery, with figures indicating that only between the end of the year and the beginning of 2021, intra-EU air traffic will partially recover, with expectations of 25-30% less aircraft movement and passengers as compared to the same months of 2019. The European Union’s reaction consists in safety related measures and packages to mitigate COVID-19’s effects on air services, airport slot allocation, air cargo operations, passenger protection, state aid. While some measures are likely to remain temporary in nature, some others, like airlines’s vouchers, will probably need more time to be further and thoroughly addressed by the EU legislator.